STRATEGI GURU AQIDAH AKHLAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN: STRATEGI GURU AQIDAH AKHLAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - , Syamsuddin, Muhammad Miftah Jauhari (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This research explores the strategy of Aqidah Akhlak teachers in improving the quality of learning in MTs. Miftahul Maarif Kudus. With a descriptive qualitative approach, this study uses documentation, observation, and interviews in exploring data and data reduction, displaying data, and drawing conclusions in analyzing data, the results of the study show: first, students' understanding, evaluation of learning outcomes, development of teacher strategies to actualize various potentials in his possession, showed good qualifications. The implementation is carried out every semester 5 times with the aim of the implementation being to get data and information about achieving competence. Second, the teacher's strategy in improving quality is by attending training, through independent learning, reading books related to her field, and increasing his knowledge through other relevant media. Third, the factors that influence the strategy are time constraints, and there are still students who have difficulty in learning. While the efforts of Aqeedah Moral teachers in improving the quality of learning are very good and endless with innovations and fun tricks in learning, for example quizzes, additional learning methods.